(untitled) (Studia theodisca, 2024)
In this essay, I examine the connection between poetry and the incomprehensibility of some of its exemplars. In particular, I examine the rise of incomprehensible poetry to being the epitome of modern poetry in the history of poetry, and I develop explanations for the significance of incomprehensible poetry in global modernity.